TANGGUNG JAWAB PENGURUS KOPERASI SIMPAN PINJAM JATENG MANDIRI YANG MENYEBABKAN KERUGIAN TERHADAP ANGGOTA BERDASARKAN UNDANG UNDANG NOMOR 25 TAHUN 1992 TENTANG KOPERASI (STUDI KASUS PUTUSAN NOMOR 45/PDT/2020/PT.SMG)” - Tommy Suhendra; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
The responsibilities of the savings and loan cooperative management are based on regulations. 25 of 1992 concerning Cooperatives, cooperatives are legal entities established by individuals or cooperative legal entities, with the separation of the wealth of its members as capital for running a business, which fulfills shared aspirations and needs in the economic, social and cultural fields in accordance with the values and principles of cooperatives. . This study aims to find out, how is the responsibility of the savings cooperative management, cooperative member rights, bankruptcy cooperative that causes losses to members based on Law No. 25 of 1992 concerning cooperatives and how the rights of members in the accountability system in savings and loan cooperatives are theoretical framework used by the author here using the theory of legal certainty, justice. , responsibility, cooperative theory The author in answering these problems uses normative legal research methods, the types of materials that the author uses are primary legal materials, secondary legal materials and non-legal materials. From the research data, it is found that many cooperative administrators must be transparent and considered competent in leading so that there is no embezzlement and money laundering crime committed by cooperative management for personal interests and has an impact on defaulting on the members of the cooperative where these members provide capital to the cooperative. Therefore, the members should be more careful in choosing the management of the cooperative and must often hold member meetings which aim to find out the remaining operating results (SHU).”